Effect of Acid-Modified Clay on the Microstructure and Performance of Starch Films - Lu, Panfang; Zhang, Min; Li, Changzhou; Liu, Zhiguang (Polymer-plastics technology and engineering, 2012)
In this work, thermoplastic starch-clay composite films were prepared via solution casting method. The use of acid-modified clay including kaolinite (HKAO) and vermiculite (HVER) improved the thermal properties of starch matrix. The structure of films was investigated and characterized by XRD and SEM techniques. The results showed that the well-dispersed clay particles were distributed in the starch matrix. According to TGA, DSC study and water absorption testing, the films with acid-modified clay exhibited higher water resistance and thermal properties compared to those of films containing pristine clay. These results provide the important information with using acid as the clay modifier to obtain starch-based materials with higher performance.